Pemanfaatan Termokopel sebagai Sensor Suhu untuk Analisis Kelarutan Zat Terlarut - Labib Muhammad Majdi; Igreya Kumendong; Izzah Huwaidah; Muhammad Fathin Abdul Aziz (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2024)
In chemical experiments, thermocouples offer a better solution than conventional thermometers with fast response, non-intrusive materials, and fairly affordable cost. This research focuses on developing a thermocouple-based solubility meter that utilises the Seebeck effect to detect temperature changes with high accuracy and fast response. This device is designed using a K-type thermocouple, Arduino UNO microcontroller, signal amplifier circuit, and LCD display. The research methodology includes design, calibration, and characterisation of the sensor to ensure accuracy and precision. Tests were conducted on sugar solution, and the results were compared with solubility reference data. The results show that the device has an average error of 0.348% and a standard deviation of 0.114%, proving its reliability in measuring solubility. The conclusion of this research is that thermocouples can be effectively utilised as temperature sensors for solubility analysis, offering a more efficient and economical solution than conventional methods.